Androgen deficiency in aging males: Translation and validation study of the iranian version - Mansoureh Ashghali-Farahani; Alice Khachian; Parya Vakilian; Mokhtar Mahmoudi (Wolters Kluwer Medknow Publications, 2021)
Background: Considering the importance of psychometric evaluation of the male sex hormone deficiency questionnaire by Iranian nurses, this study aimed to determine the translation and validation of the Iranian version of the Androgen Deficiency in Aging Males (ADAM) questionnaire. Materials and Methods: This study was cross-sectional. After obtaining permission from the instrument maker, translating it into Farsi, retranslated it into English, and determining validity and reliability. The study population was 200 Iranian men who admitted to hospitals affiliated with Iran University of medical science and were older than 50 years and selected by convenience sampling method. They were evaluated and monitored based on the Iranian version of the ADAM questionnaire. Sensitivity and specificity were assessed and analyzed by Rock Chart analysis. Descriptive and analytical statistical tests were used at a significant level of 0.05. Results: Findings showed that the Iranian version of the ADAM questionnaire had good face validity. Results showed that Cronbach's alpha in this questionnaire was 0.93, which indicates high reliability, and all the valid questionnaires were reported for the Scale-Content Validity Index (SCVI) calculation. Hence, the questionnaire has good content validity. The Iranian version of the ADAM questionnaire has a sensitivity of 93.85' and a specificity of 77.14' at the cut-off point of 2.2, indicating high sensitivity and specificity. Conclusions: The Iranian version of the ADAM questionnaire is valid and reliable and has high sensitivity and specificity. Nurses can also use it as an adjunctive scale to screen andropause men over 50 years of age.